The South versus the North, the Piarists versus the Jesuits: the educational dispute based on nature in the mid-eighteenth century in the Polish Lithuanian Commonwealth. - Orzel, Joanna (Paedagogica Historica, 2019)
Education in the Polish-Lithuanian Commonwealth was primarily held in colleges led by Jesuits and Piarists. There were disputes between them – regarding both the content and methods of teaching, as well as the prestige of the institutions and teachers employed in them. The competition at the symbolic level of two orders was also unitary – in the middle of the eighteenth century a dispute arose between two representatives of these orders: the Piarist Ubaldo Mignoni and the Jesuit Franciszek Bohomolec. Mignoni in his essay Noctium Sarmaticarum vigiliae used the concept of geographical determinism and climate theory to prove that not all peoples, including the peoples of the North (also the Polish-Lithuanian Commonwealth), were capable of developing science and art at the highest level. The next year Jesuit Franciszek Bohomolec in his work Pro ingeniis Polonorum oratio opposed the theory of climate as the decisive factor of intellectual and artistic development of individual societies. The main part of the article is the analysis of the arguments used by those writers. The paper ends with a similar education dispute with the theory of climate in the Apennine Peninsula between Jérôme Lalande and Michele Torcia.